Wanita Penjaja Agama Kepemimpinan Sister Aimee Semple McPherson dalam Novel: Elmer Gentry, Oil!, dan The Loved One - Nursaktiningrum Nursaktiningrum (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2010)
This article studies how three famous American writers portray Sister McPherson (1890-1944), a controversial female religious leader, in their novels. Placing the novels written by Lewis, Sinclair, and Waugh in the context of American society, this study aims to reveal how Sister McPherson crossed gender boundaries and reinvented tradition in American religious institutions. By combining religious teachings and the advancement of popular culture, she broke the old religious tradition and succeeded in popularizing the religion she embraced.